PENERAPAN STRATEGI SEGMENTASI PEMASARAN DALAM PROGRAM TALK SHOW KICK ANDY DAN MATA NAJWA (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2020)
The initial step in marketing is market segmentation which is useful for dividing consumers in the market and choosing one of the segments that is the target market. This study aims to find a comparison of marketing segmentation strategies in television talk show programs and find out the similarities, strengths, and weaknesses in implementing marketing segmentation strategies. The research method used is descriptive qualitative, using the main sources namely the Executive Producer of the Mata Najwa talk show program, Mrs. Citra Buana and the Senior Producer of Metro TV, Mr. Daingin Surya Paloh as primary sources and secondary sources in the form of books, internet, and airing talk shows "Mata Najwa "and" Kick Andy "themselves. The results found a comparison of the types of marketing segmentation strategies used between the Mata Najwa and Kick Andy talk show programs, which were the same, namely: (1) demographic segmentation with ages between 19 years and 50s and the lowest level of senior high school/student education; (2) Geographic Segmentation is the national territory of Indonesia and penetrated internationally; (3) Demographic and Geographic Segmentation takes the themes of the talk show that is raised on actual issues related to public policy, political issues, legal and social policies by bringing in figures who are currently in public discussion or inspiring themes. The difference is the Mata Najwa program raises heavy topics, issues that are developing today, while the Kick program raises inspirational themes.Keywords: Marketing Segmentation Strategy, Talk Show, Mata Najwa, Kick Andy